Wound healing potential of aloe vera in climbing perch (Anabas testudineus). - Selamat, Siti Suzana; Hashim, Kalthum; Matori, Mohd Fuad (2010)
Fresh gel portion of Aloe vera leaves was evaluated for the wound healing potential in climbing perch (Anabas testudineus). Fifteen adult climbing perch were divided into three groups. Group 1 received Aloe vera gel, group 2 received Betadine® antiseptic ointment (positive control) and group 3 received no treatment (negative control). Wound was created at the flank area using a punch biopsy (8 mm in diameter). One topical application was applied on the wound. Assessment of healing progress was carried out on day 10. Gross observation and histological studies were carried out. There was no significant difference in wound reduction among the groups. However, group 2 showed highest rate of healing followed by group 1 and group 3, and groups 1 and 3 had similar rate of healing. Histological examination on cellular activity of healing process showed increased thickness of epithelium layer, infiltration of inflammatory cells, presence of fibroblast cell and rearrangement of the cell.